Depth Perception Improvement in Collegiate Baseball Players with Vision Training. - Clark, Joseph F.; Graman, Patricia; Ellis, James K. (Optometry & Visual Performance, 2015)
Background: Vision training is rapidly becoming a component of sports enhancement, but quantifiable and validated improvement in visual performance has not been clearly demonstrated in high-caliber and/or collegiate athletes. We have performed vision training for the last three seasons on the University of Cincinnati baseball team's hitters. The goal for the work was performance enhancement, and for monitoring purposes, we measured stereopsis pre- and post-vision training. Methods: From the preseason (January) 2011 through to the end of the season (May) 2013, all hitters in the University of Cincinnati baseball team underwent regular vision training. Out-of-season training was 20 minutes twice per week, and in-season was 20 minutes once per week. Traditional stereopsis (Stereo Fly) was performed and recorded. Vision training typically consisted of: Dynavision light board, Brock string, strobe glasses, Eyeport, saccades, and near-far. Results: The players consistently came into the season with stereopsis of 23.7 ± 1.0 mm, and six weeks of training increased this stereopsis to 36.9 ± 0.49 mm (p<0.0001). Discussion: There was a consistent and significant improvement in stereopsis measured by Stereo Fly with the baseball team after 6 weeks of vision training. Equally, the stereopsis returned to baseline out of season. Temporal benefits seemed to continue post-6 weeks of vision training. We conclude that in a population of healthy and high-caliber athletes, stereopsis can improve with training and suffer from detraining effects as well. We suggest that vision training for sports that require good stereo acuity be considered.